Inklusi Keuangan Melalui Program Layanan Keuangan Digital dan Laku Pandai - Sastiono, Prani; Nuryakin, Chaikal (UI Scholars Hub, 2019)
This study aims to analyse the inclusion rate of two programs, namely Layanan Keuangan Digital (LKD) and Laku Pandai. We found that inclusion rate of LKD program and Laku Pandai program are 28% and 43% respectively when we define inclusion as use of service (access inclusion). However, the rate falls to 5% and 25% respectively when we define inclusion as account ownership. Laku Pandai program has advantages in increasing financial access of people who live in rural area, have low education, and generate low income. We also found that knowledge/certainty in transaction costs (for LKD) and size of access costs in the form of transaction costs and transportation costs (for Laku Pandai) are important determinants of account ownership.